Research in the history of economic thought and methodology. Vol. 40, including a symposium on the work of William J. Baumol: heterodox inspirations and neoclassical models - Fiorito, Luca; Scheall, Scott; Suprinyak, Carlos Eduardo (Research in the history of economic thought and methodology ;, 2022)
The centerpiece of Volume 40B of Research in the History of Economic Thought and Methodology is a symposium on the work of William Baumol, edited by Erwin Dekker. The symposium includes contributions from Alex Tabarrok, Jochen Hartwig and Hagen M. Krämer, Alexandre Chirat, Victor A. Beker, Caroline Colton, Magnus Henrekson and Mikael Stenkula, and Anna Noci. Volume 40B also features new general-research essays from Juan Pablo Castilla and Fabrizio Bientinesi.